Short communication: New report of Aedes albopictus in Souk Ahras, Northeast Algeria - Kaouther Hamaidia; Noreddine Soltani (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Hamaidia K, Soltani N. 2021. Short communication: New report of Aedes albopictus in Souk Ahras, Northeast Algeria. Biodiversitas 22: 2901-2906. The present paper reports the occurrence of Aedes albopictus (Skuse), an aggressive Asian tiger mosquito in the city of Souk-Ahras (Northeast of Algeria). A “26 April” estate’ inhabitants (Souk-Ahras province) have reported unusual daytime bites by a striped mosquito. On early September 2020, an intensive field inspection was carried out for potential mosquito breeding sites in the locations around the city. A total of 105 specimens (8 larvae, 24 pupae and 73 adults) of Ae. albopictus were collected in a pile of old tyres in a residential garden. After previous records of this species in Algeria, this is the first evidence of its presence in Souk-Ahras province, and the findings enhance combined public participation with professional validation in surveillance of vector borne-diseases programs with emphasis on the need for sensitising citizens about controlling this important vector.